Circular RNA CHST15 Sponges miR-155-5p and miR-194-5p to Promote the Immune Escape of Lung Cancer Cells Mediated by PD-L1 - Yang, Jianru; Jia, Yang; Wang, Bing; Yang, Shengrong; Du, Kun; Luo, Yujie; Li, Yunhe; Zhu, Bing (Frontiers in Oncology, 2021)
Background: Up-regulated CircCHST15 was found in lung cancer, but, its effect on lung cancer is unknown. In this study, we tried to explore the role of CircCHST15 on lung cancer. Methods: After miR-155-5p and miR-194-5p were proved to be targeted byCircCHST15, the target of miR-155-5p and miR-194-5p was also verified by bioinformatics and luciferase assays. The correlation between CircCHST15 and PD-L1 was analyzed by Pearson analysis. The viability and proliferation of lung cancer cells were detected by CCK-8 and colony formation. After the lung cancer (subcutaneous-xenotransplant) mice model established, the T cell subtype and the related-cytokines in mice tumor tissues were detected by flow cytometry and ELISA. Also, the expressions of CircCHST15, miR-155-5p, miR-194-5p, immune-related, and proliferation-related factors in the lung cancer cells or mice tumor tissues were detected by immunohistochemical, RT-qPCR, or Western blot. Results: CircCHST15 and PD-L1 highly expressed in lung cancer, a positive correlation existed between CircCHST15 with PD-L1. CircCHST15 targeted miR-155-5p and miR-194-5p which further targeted PD-L1. Lung cancer cell viability and proliferation were enhanced by miR-155-5p and inhibited by miR-194-5p. CircCHST15 located in the cytoplasm promoted tumor growth; decreased the levels of miR-155-5p and miR-194-5p; promoted the expressions of PD-L1, Ki-67, PCNA, CCL17, CCL22, IFN-γ, TNF-β, and IL-10. Also, CircCHST15 decreased the CD8+ cells in mice blood and tumor, while increased the Tregs in mice tumors. PD-L1 inhibitor had an opposite effect with CircCHST15 on mice tumors. Conclusion: CircCHST15 sponged miR-155-5p and miR-194-5p promoting the PD-L1-mediated immune escape in lung cancer.